The Future of Guidance and Counselling in the 21st Century in Nigeria: Changing Face-to-Face Counselling through Cyberspace Counselling - Muraina, Kamilu Olanrewaju; G, Saleh Musa; Kabir, Zahrau Muhammad (Universitas Terbuka, 2020)
The use of technology in all spheres of lives has brought about significant changes worldwide. The use of internet has replaced the face-to-face counselling in the western world. The future is being shaped by current and emerging technologies that are drastically changing the way in which people interact. Such changes are as a result of development in the field of science and technology. Consequently, cyberspace counselling is at the forefront of the paradigm changes that are shaping the future of face-to-face counselling. This paper reflects on the potential benefits of cyberspace counselling in the 21st century, its implication, challenges and prospects for counsellors and the counsellees in Nigeria. Building upon this, the paper also concludes why these technologies can change theface-to-face traditional counselling to cyberspace counselling thereby making both counsellors and clients in the realm of counselling context.